¿Las guías de evaluación visual son efectivas para detectar diferencias en la calidad del suelo? - Sainz, Daiana Soledad; Contreras, Cecilia Ines; Rey, Rocio Belen; Becerra, Juan Francisco; Carfagno, Patricia (AAPRESID, 2024)
Poster